2007
DOI: 10.1016/j.otohns.2007.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Freedom North American Clinical Trial

Abstract: Higher stimulation rates do not necessarily result in improved performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 8 publications
4
72
1
1
Order By: Relevance
“…Preference of the majority of subjects in this study for 500 pps/ch rate in quiet, noise and overall is somewhat consistent with the results of Balkany et al (2007), where 67% of the subjects preferred the slower strategy (ACE) over the faster rate strategy (ACE RE) with the majority of subjects preferring the slowest rate in each strategy (500 pps/ch in ACE and 1800 pps/ch in ACE RE). However, in contrast to the present study, there was no significant effect of rate on the speech perception outcomes in their study.…”
Section: Clinical Ramificationssupporting
confidence: 87%
See 1 more Smart Citation
“…Preference of the majority of subjects in this study for 500 pps/ch rate in quiet, noise and overall is somewhat consistent with the results of Balkany et al (2007), where 67% of the subjects preferred the slower strategy (ACE) over the faster rate strategy (ACE RE) with the majority of subjects preferring the slowest rate in each strategy (500 pps/ch in ACE and 1800 pps/ch in ACE RE). However, in contrast to the present study, there was no significant effect of rate on the speech perception outcomes in their study.…”
Section: Clinical Ramificationssupporting
confidence: 87%
“…The findings of previous research (Weber et al, 2007;Cochlear Ltd. 2007, Reference Note 1; Balkany et al, 2007) suggest that for majority of the subjects using Nucleus implants, stimulation rates between 500 pps/ch and 1200 pps/ch should be tried. The present investigation's findings are compatible, suggesting that clinicians should program Nucleus recipients with the rates 500 pps/ch or 900 pps/ch.…”
Section: Clinical Ramificationsmentioning
confidence: 97%
“…American clinical trial' (Balkany et al, 2007), 'The Cochlear Implant Clinic of the Royal Victorian Eye and Ear Hospital' in Melbourne Australia (Dowell, Hollow, & Winton, 2003;Flynn, Dowell, & Clark, 1998); 'The Midland Cochlear Implant Programme' in the UK (Proops et al, 1999); 'The Vienna Cochlear Implant Programme' in Austria (Hamzavi, Franz, Baumgartner, & Gstoettner, 2001); 'The University of Iowa CI Program' in the US (Tyler, Parkinson, Woodworth, Lowder, & Gantz, 1997); and 'The CI centre' in Nijmegen in the Netherlands (van Dijk et al, 1999). This current study provides results for adult CI recipients from the Southern Cochlear Implant Programme (SCIP), New Zealand, for the perception of speech in both quiet and noise.…”
Section: Rationalementioning
confidence: 99%
“…Figure 1 shows that due to a current spread in the cochlea and by using a single-channel rate of 900 pulses/s, an SGN can be exposed to an effective rate of 7200 pulses/s when stimulation is delivered by eight electrodes. Some studies have shown that subjects prefer high single-channel stimulation rates in the range of 1700 to 4000 pulses/s (Nie et al 2006;Verschuur 2005;Kiefer et al 2000;Loizou et al 2000), others demonstrated no benefit (Friesen et al 2005;Plant et al 2002;Weber et al 2007;Holden et al 2002;Plant et al 2007;Arora et al 2009), while other research indicates that low to moderate stimulation rates, i.e., 250 to 500 pulses/s, work best (Balkany et al 2007;Vandali et al 2000). Significantly, most of these studies report large variance between the performance of individuals as a function of the stimulation rate.…”
Section: Introductionmentioning
confidence: 99%